Green Finance and SME Growth in Morocco: The Mediating Role of Green Investment - Mejji, Omar; Darkaoui, Abdelhadi (International Review of Management and Marketing, 2026)
This study examines the impact of green finance on SME growth by incorporating green investment as a mediating variable within the context of Moroccan SMEs. Drawing on the Resource-Based View (RBV), the study explains how access to environmentally oriented financial resources may stimulate sustainable investment practices and contribute to organizational growth. A quantitative survey approach was employed, and data were collected from 116 Moroccan SMEs through a self-administered questionnaire administered to business owners and managers. The data were analyzed using structural equation modeling with the partial least squares (SEM-PLS) technique under R software. The results indicate that green finance has a positive and significant effect on green investment. In addition, green investment positively and significantly influences SME growth, while the direct effect of green finance on SME growth remains relatively limited. The mediation analysis confirms that green investment partially mediates the relationship between green finance and SME growth. These findings highlight the strategic importance of environmentally sustainable investments as a transmission mechanism through which green finance may contribute to SME development and competitiveness in emerging economies.